The politics of Islamic reassertion - Ayoob, Mohammed 1942- (Routledge library editions: politics of Islam, 2013)
The Iranian Revolution has catalysed the preconceptions holding sway in the Western World about the character of Islam and its politics, based as they are on a mixture of imagined cultural superiority and a latent fear of a resurgence similar to the Arab conquests of the seventh and eighth centuries of the long Ottoman domination of Eastern Europe. This book constitutes a counterweight to such monolithic perceptions of Islam. It surveys the nature of opinion and of government in the larger Muslim regions of the world, and the position of Muslims in states where they are not the domina.